2020
DOI: 10.1039/d0ta01968b
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-tolerant and high-quality α-CsPbI3 films for efficient and stable perovskite solar modules

Abstract: Crown ether effectively stabilizes the cubic phase of CsPbI3 to inhibit the moisture invasion and phase transformation of CsPbI3 films, producing large-area devices and improving device performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 54 publications
1
82
0
Order By: Relevance
“…The 1 H NMR spectra of CH 2 group for Crown in solutions show distinguishable chemical shifts when respectively mixing with CsI, PbI 2, and CsI+PbI 2 , demonstrating a stronger interaction with Cs + ion than that with Pb 2+ ion due to the higher nucleophilicity of oxygen in Crown with Cs + ions. [ 31 ] In this regard, pure FAPbI 3 films were produced without introducing Cs + cations (detailed experiment as in Supporting Information), in which almost indistinguishable crystallinity and PbI 2 species were observed no matter with or without Crown (Figure S6a, Supporting Information). And the corresponding PSCs also displayed the similar low efficiencies (Figure S6b, Supporting Information) and Table S1, Supporting Information, which demonstrated the little influence of Crown on the synthesis of FAPbI 3 films in spite of the interaction between Pb 2+ cations and Crown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H NMR spectra of CH 2 group for Crown in solutions show distinguishable chemical shifts when respectively mixing with CsI, PbI 2, and CsI+PbI 2 , demonstrating a stronger interaction with Cs + ion than that with Pb 2+ ion due to the higher nucleophilicity of oxygen in Crown with Cs + ions. [ 31 ] In this regard, pure FAPbI 3 films were produced without introducing Cs + cations (detailed experiment as in Supporting Information), in which almost indistinguishable crystallinity and PbI 2 species were observed no matter with or without Crown (Figure S6a, Supporting Information). And the corresponding PSCs also displayed the similar low efficiencies (Figure S6b, Supporting Information) and Table S1, Supporting Information, which demonstrated the little influence of Crown on the synthesis of FAPbI 3 films in spite of the interaction between Pb 2+ cations and Crown.…”
Section: Resultsmentioning
confidence: 99%
“…Understandably, as Crown could not doped into the crystal lattice, after crystallization, the molecules would self‐assembled on the surface and grain boundaries through the strong interactions with metal ions (Figure S10, Supporting Information). [ 31 ] X‐ray photoelectron spectroscopy (XPS) measurements were further performed to investigate the detailed chemical states in the Crown‐manipulated perovskite films (Figure 2c,d). The XPS doublet peaks of Cs 3d 3/2 and Cs 3d 5/2 were detected at the energy of 738.4 and 724.5 eV in the FACsPbI 3 film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Chen et al proposed a surface passivation method of drop-casting an 18-crown-6 ether (Crown) lm on the CsPbI 3 lm surface. 100 As shown in Fig. 11d, pristine a-phase CsPbI 3 has high sensitivity to humidity, transferring to the a-dor d-phases with H 2 O molecules attacking the surface.…”
Section: Stability Of Low Light Opvsmentioning
confidence: 95%
“…To obtain a stable perovskite phase, the adoption of mixed cation perovskites or inorganic perovskites has been established as a promising strategy under 1 sun condition, 49,50 which may be also effective in the stability enhancement of indoor PPVs. 100,101 Singh et al reported that the Cs-tuned Cs x (FA 0.83 MA 0.17 ) (1Àx) Pb(I 0.83 Br 0.17 ) 3 (where x is the mole fraction of Cs) perovskite devices can achieve an optimal PCE of $17% under AM1.5G condition when x ¼ 0.05 and should also obtain decent device performance under low light conditions considering its extraordinary stability in the ambient atmosphere. 101 This mixed-halide PPV device showed no signicant degradation in device performance upon exposure to ambient air under dark conditions with RH 20-35% (see Fig.…”
Section: Stability Of Low Light Opvsmentioning
confidence: 99%